A clinical case of a sepsis-like course of coronavirus infection on the background of primary metabolic gout - A. O. Mikhailov; S. A. Sokotun; A. I. Dubikov; N. G. Plekhova; A. I. Simakova; S. A. Petukhova; I. V. Ubozhenko; I. V. Volodina (Лечащий Врач)
Background. It is often believed that gout is an uncommon disease and therefore of little interest to general practitioners. However, the incidence of gout in the world is steadily increasing, which is explained by the increase in the population of persons with hyperuricemia. Allergic reactions, non-compliance with the treatment regimen, drug interactions, and sometimes the ineffectiveness of hypouricemic therapy leads to a severe course of the disease. Gout often occurs in combination with diseases such as obesity, diabetes, arterial hypertension. At present, the course of coronavirus infection against the background of gout is of great interest. Taking into account the Interim Guidelines of the Ministry of Health of Russia, version 17 of December 14, 2022 ″Prevention, diagnosis and treatment of a new coronavirus infection (COVID-19)″, patients with immunoinflammatory rheumatic diseases represent special groups of patients. In case of infection of such patients with the SARS-CoV-2 virus, it is necessary to interrupt treatment with standard basic anti-inflammatory drugs (methotrexate, leflunomide, azathioprine), genetically engineered biological drugs (tumor necrosis factor-α inhibitors, IL-6, IL-17, IL-12 /23, IL-23, T-cell co-stimulation blockers, anti-B cell drugs (rituximab, belimumab) Hospitalization should be carried out only for urgent indications with the provision of laboratory data on the absence of SARS-CoV-2 infection.   Objective. This article discloses the details course of coronavirus infection in a patient with immune-mediated gout with an allergy to all anti-gout drugs and the absence of specific hypouricemic therapy for more than 30 years.   Results. The severity of the condition was determined by bleeding from a steroid gastric ulcer, adrenal insufficiency secondary to regular and uncontrolled intake of corticosteroids and non-steroidal anti-inflammatory drugs. Also, the condition was regarded as severe due to the symptoms of intoxication, hyperthermia, asthenovegetative syndrome, diarrheal syndrome. The patient was visualized chronic infection of the bloodstream in the form of vegetation on the tricuspid valve, increased markers of sepsis and systemic inflammation, which was interpreted as a manifestation of bacterial sepsis. However, due to the lack of dynamics against the background of ongoing antibiotic therapy – the persistence of fever, an increase in the number of tophi in the area of the hands and feet, the progression of arthralgia, it was assumed that this is due to the underlying disease and the development of an independent immune mechanism for damage to internal organs and the deposition of tophi on the tricuspid valve. Taking into account the clinical picture of the disease and the data of laboratory and instrumental examination, the diagnosis of bacterial sepsis was excluded and the condition was regarded as an immune-mediated sepsis-like severe course of gout in the absence of treatment with secondary amyloidosis of internal organs and deposition of tophi, including on the tricuspid valve. Olokizumab 160 mg/ml – 0.4 ml subcutaneously was prescribed for treatment in order to stop the systemic immune inflammatory response. After the introduction of the drug, there was a gradual normalization of body temperature, a decrease in pain, articular syndrome and an indicator of the level of IL-6.   Conclusion. Thus, olokizumab therapy brought a significant positive effect and contributed to the stabilization of the patient's condition. It should be noted that in patients with immune-mediated diseases, infectious acute diseases can occur in a sepsis-like form and should be assessed comprehensively and early preventive anti-inflammatory therapy initiated.